2024
DOI: 10.1002/eat.24122
|View full text |Cite
|
Sign up to set email alerts
|

Examining the placement of atypical anorexia nervosa in the eating disorder diagnostic hierarchy relative to bulimia nervosa and binge‐eating disorder

K. Jean Forney,
Taylor L. Rezeppa,
Naomi G. Hill
et al.

Abstract: ObjectiveSome individuals meet the criteria for atypical anorexia nervosa and another eating disorder simultaneously. The current study evaluated whether allowing a diagnosis of atypical anorexia nervosa to supersede a diagnosis of bulimia nervosa (BN) or binge‐eating disorder (BED) provided additional information on psychological functioning.MethodsArchival data from 650 university students (87.7% female, 69.4% white) who met Eating Disorder Diagnostic Survey for DSM‐5 eating disorder criteria and completed q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…However, Keegan and Wade (2024) found that among individuals with BN receiving outpatient treatment, higher levels of readiness and confidence to change had steeper decreases in symptoms; no such relationship was observed among individuals with atypical AN. In a study of university students, Forney et al (2024) found that a large number of individuals met criteria for atypical AN and either BN or binge-eating disorder (BED) and examined advantages and disadvantages of allowing a diagnosis of atypical AN to supersede ("trump") a diagnosis of BN or BED. Although findings were mixed, the results suggested that the current DSM-5 hierarchy, in which a diagnosis of BN or BED supersedes that of atypical AN (and other OSFEDs), should be maintained.…”
mentioning
confidence: 99%
“…However, Keegan and Wade (2024) found that among individuals with BN receiving outpatient treatment, higher levels of readiness and confidence to change had steeper decreases in symptoms; no such relationship was observed among individuals with atypical AN. In a study of university students, Forney et al (2024) found that a large number of individuals met criteria for atypical AN and either BN or binge-eating disorder (BED) and examined advantages and disadvantages of allowing a diagnosis of atypical AN to supersede ("trump") a diagnosis of BN or BED. Although findings were mixed, the results suggested that the current DSM-5 hierarchy, in which a diagnosis of BN or BED supersedes that of atypical AN (and other OSFEDs), should be maintained.…”
mentioning
confidence: 99%